مرجعيات البحث اللساني ومصادره في دراسات توشيهيكو إيزوتسو القرآنية: (Linguistic Research References and Its Sources in Toshihiko Izutsu's Qur'anic Studies) - (Abdulrahman ALHAJ), عبد الرحمن الحاج (At-Tajdid - Intellectual Refereed Journal, 2022)
Abstract Izutsu’s studies in understanding the Qur’an constitute a milestone in the history of modern studies, with the interest they received from Muslim researchers. These studies represent one of the main platforms that can form a basis for academic discussion on the issue of dealing with western modern approaches and their suitability for interpretation and analysis of Arabic religious texts and their intrepretations, and inparticular the Holy Qur’an. This research traced the development of studies and academic works carried out by Izutsu during his lifetime. It tried to understand the motives that led him to research on the Holy Qur’an, the reason for choosing certain tools and sources, the conclusions he reached, and goals Which he was seeking to achieve in these studies. It is apparent that the purposes of the Qur’anic study are philosophical. It is to understand the Arab and Islamic culture and the Arab psyche that created and formed this culture. Hence, Izutsu's research on the Holy Qur'an had focused on "worldview" and "moral concepts", which are purely philosophical topics. Nonetheless, the usefulness and the appropriateness of this type of linguistic study of the Holy Qur'an is still viewed with scepticism. Key words: Izutsu, linguistics, the Qur'an, orientalism.